113k views
4 votes
Can someone help me out with this question plz

Can someone help me out with this question plz-example-1
User Malcom
by
5.9k points

1 Answer

3 votes

Answer:


\left(s\cdot t\right)\left(x\right)=2x^2+12x+16


\left(s-t\right)\left(x\right)=-x


\left(s+t\right)\left(4\right)=20

Explanation:

Given functions are:


s\left(x\right)=x+4


t\left(x\right)=2x+4

Then
\left(s\cdot t\right)\left(x\right)=s\left(x\right)\cdot t\left(x\right)

or
\left(s\cdot t\right)\left(x\right)=\left(x+4\right)\left(2x+4\right)

or
\left(s\cdot t\right)\left(x\right)=2x^2+4x+8x+16

or
\left(s\cdot t\right)\left(x\right)=2x^2+12x+16

---------

Similarly


\left(s-t\right)\left(x\right)=s\left(x\right)-t\left(x\right)

or
\left(s-t\right)\left(x\right)=\left(x+4\right)-\left(2x+4\right)=x+4-2x-4

or
\left(s-t\right)\left(x\right)=-x

---------

Similarly


\left(s+t\right)\left(4\right)=s\left(4\right)+t\left(4\right)=\left(4+4\right)+\left(2\left(4\right)+4\right)=\left(8\right)+\left(12\right)=20


\left(s+t\right)\left(4\right)=20

User Skeniver
by
5.7k points